(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The electronic payment systems are considered the most important infrastructure for the work of banks, particularly after a steady and remarkable development in information and communication technology, Which created the reality of the work of the infrastructure for these systems and these systems also become one of the most important components of infrastructure for the work of banks, cause it is one of the most important channels through which the transfer of cash, financial instruments between financial institutions in general and banking in particular. In order to achieve the objectives of the research, the most important to identify the concept of electronic payment systems, and its divisions, and the statement of the concept of banking performance, and get to know his standards, and to identify the elements of efficiency in the banking service, the research has included the relationship between the electronic payment systems as an independent variable, and the efficiency of the banking performance as the dependent variable. The research sample has included of payments department in the Central Bank of Iraq, and the department of payments in each of Al- Rafidain Bank and AL- Rasheed Bank, additionally to the Trade Bank of Iraq, and Ashur International Bank for Investment, and Iraqi Middle East Investment Bank, Bank of Baghdad, and National Bank of Iraq, Commercial Bank of Iraq and Bank of the Audi branch of Iraq, a sample of (72) employees was chosen and supplied with questionnaires. The researchers has reached several conclusions such as: • The electronic payment systems contribute to reducing the time and costs required for transfers of money and financial instruments, also it is contributed to innovation new methods in completing the banking business, and reduce the risks of currency trading traditional form. • These systems have contributed to pay price for goods and services in a smooth and safe methods better than before, which reflected positively on the efficiency of the banking performance. • The results of the statistical analysis of the answers to the research sample have been confirmed on the existence of a correlation as a direct correlation and significant morale among the electronic payment systems, with banking performance efficiency, The results of the statistical analysis of for the answers to the research sample confirmed the presence of significant effect relationship for the electronic payment systems, on at the efficiency of the banking performance, as the beta coefficient signals are positive which means there is a positive effect. The researchers has recommended a number of recommendations including: • The need for the Central Bank of Iraq worthwhile electronic payment systems through the modernization of these systems and development, and work on the activation of non-active systems, as these systems become of the most important channels for the transfer of money, and financial instruments between financial and banking institutions. • Banks need to rely on payment systems in the transfer of operations, clearing and settlement, because the services provided to customers is characterized by these systems, precision and speed, these systems also contribute to customer satisfaction, and increase awareness of the financial and banking.